Pengaruh Influencer Terhadap Brand Awareness dari Produk Skincare - Anthony, Nicholas; Prabaseno, Ignatius Wisnu; Hellyani, Catharina Aprilia (Fakultas Ekonomi Universitas Kadiri, 2023)
This journal discusses the development of the cosmetic world which is now starting to use various ways to carry out promotions, one of which is by using the help of influencers. With the help of influencers, it is hoped that brand awareness will be created among consumers. This research examines whether influencers can increase brand awareness for consumers.This study uses the literature review method which contains previous research that has conducted empirical and literature tests on the relationship of influencers to company brand awareness.The results of the literature review state that influencers can increase brand awareness of a product if it is accompanied by the experience and original character of the influencer. In addition, the level of entertainment in influencer content has no significant effect on building brand awareness. Based on previous research, it can be concluded that influencers are able to build brand awareness from consumers of cosmetic brands.